2007
DOI: 10.1093/brain/awm007
|View full text |Cite
|
Sign up to set email alerts
|

Altered orbitofrontal sulcogyral pattern in schizophrenia

Abstract: Orbitofrontal alteration in schizophrenia has not been well characterized, likely due to marked anatomical variability. To investigate the presence of such alterations, we evaluated the sulcogyral pattern of this 'H-shaped' sulcus. Fifty patients with schizophrenia (100 hemispheres) and 50 age- and gender-matched control subjects (100 hemispheres) were evaluated using 3D high-spatial resolution MRI. Based on a previous study by Chiavaras and Petrides (2000), the sulcogyral pattern of the 'H-shaped' sulcus, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
131
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 55 publications
(61 reference statements)
21
131
5
Order By: Relevance
“…In addition, altered sulcogyral patterns in the orbitofrontal cortex (OFC), a key brain region involved in odor hedonic processing and sensory integration, were found to differentiate schizophrenia patients and individuals who convert to schizophrenia from non-converters and controls (Chakirova, Welch et al, 2010; Nakamura, Nestor et al, 2007). Therefore, odor valence measures, reflective of both hedonic disturbance and orbitofrontal impairment, could have predictive utility in identifying those at risk for the development of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, altered sulcogyral patterns in the orbitofrontal cortex (OFC), a key brain region involved in odor hedonic processing and sensory integration, were found to differentiate schizophrenia patients and individuals who convert to schizophrenia from non-converters and controls (Chakirova, Welch et al, 2010; Nakamura, Nestor et al, 2007). Therefore, odor valence measures, reflective of both hedonic disturbance and orbitofrontal impairment, could have predictive utility in identifying those at risk for the development of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…5), as well as those with ADHD (McAlonan et al, 2005; Okugawa et al, 2007; Seidman et al, 2011; Silk et al, 2009); however, there is some indication that there may also be some increases in gray matter volume in ASD patients (Bonilha et al, 2008; Hazlett et al, 2006; McAlonan et al, 2005). There are also modest alterations in gyral/sulcal patterns (Nakamura et al, 2007; Nordahl et al, 2007; Watanabe et al, 2014). Finally, diffusion tensor-based analysis of MRI data (DTI) indicates that major corticocortical fiber tracts are disrupted in the brains of individuals with ASD, ADHD, and SCZ (Ashtari et al, 2005; Conturo et al, 2008; Phillips et al, 2011; Silk et al, 2009).…”
Section: 22q11ds: a Paradigmatic Disorder Of Cortical Circuit Devementioning
confidence: 99%
“…In non-clinical populations, Type I patterns tend to be the most common (56% of hemispheres), Type II slightly less common (30% of hemispheres), and Type III relatively rare (around 14% of hemispheres). In 2007, Nakamura et al observed that the frequency of expression of these patterns differs in populations with schizophrenia, where Type I patterns become significantly less common and rare, Type III patterns increase in frequency 11 . Such findings were corroborated by other research groups 12,13 .…”
mentioning
confidence: 99%